The validation of the CTS-6 Evaluation Tool for diagnosing carpal tunnel syndrome (CTS) in Thai wheelchair users - Montana Buntragulpoontawee; Siam Tongprasert; Jiraporn Khorana; Kittipong Kitisak; Waris Karinuntakul; Sineenard Pornjaksawan; Phichayut Phinyo (PLoS ONE, 2025)
Objective The CTS-6 Evaluation Tool is a clinical diagnostic tool for carpal tunnel syndrome. It was originally developed using data from non-disabled individuals and has never been validated in different population. This study aimed to validate CTS-6’s diagnostic performance at a cutoff score of 12 in a new population of wheelchair users. Methods The participants were 54 Thai wheelchair users from a university hospital’s neuropathy registry. Those with a history of nerve injury, fracture, neuropathy, or pregnancy were excluded from the study. All underwent clinical exam, CTS-6, and electrodiagnosis (blinded evaluator). Carpal tunnel syndrome was diagnosed based on clinical symptoms and electrodiagnostic criteria. Results Of 54 participants, 13 were female (24.1%) with an average age of 46.9 (SD 12.2) years, and 18 (33.3%) participants had carpal tunnel syndrome. Duration of disability (years) was significantly longer in cases; median 24 (Q1 19.0, Q3 28.9), p < 0.001. Discriminative performance: Area under the receiver operating curve 0.935 (95%CI:0.891-0.978). At the 12 cutoff point, the sensitivity was 43.8% (95%CI:26.4-62.3%) and the specificity was 100.0% (95%CI:94.8-100.0%). A lower cutoff point showed increased sensitivity and specificity. Symptomatic subgroup analysis showed similar diagnostic performances. Conclusion The CTS-6 Evaluation Tool is a simple clinical diagnostic tool that does not require sophisticated investigation. The CTS-6’s discriminative ability remains strong. The diagnostic performance at a cutoff score of 12 showed moderate sensitivity and high specificity. Applying a cutoff score of 12 could help rule in the diagnosis where access to electrodiagnosis is limited. A lower cutoff score that is 7.5 could be applied as a screening test to rule out the diagnosis, as it provides moderately higher sensitivity at the cost of increased false positives.